Chalcis/Qinnasrin (Syrie) De l'âge du Bronze à l'époque mamelouke. Qinnasrin II - Rousset, Marie-Odile (Archéologie(s), 2021)
The syro-french archaeological research mission of Qinnasrin has worked between 2008 and 2010 on the site of al-'Iss (Northern Syria, Aleppo region), in the village itself and in the imediate surroundings. These fieldworks have been funded by the French Commission of excavations from the Ministry of Foreign Affairs, the Fundation Max van Berchem, the French National Center of Scientific Research and the General Directory of Antiquities and Museums of Syria. Established since the end of the 3rd millennium BC, Qinnasrin is an important road and military junction, dominating a fertile plain on the edge of the steppe and irrigated agricultural areas. Renamed Chalcis by the Greeks, it was, in Roman times, the seat of a kingship and minted coins. It plays an essential role in the fortification system of Northern Syria set up by Justinian against the Persians and then during the conquest of Northern Syria by the armies of Islam. Closely linked to Aleppo, it declined, to its benefit, from the middle of the 10th century and fell into oblivion around the 14th century. This book provides an overview and synthesis of the textual and archaeological sources. It presents the documentation constituted by the pedestrian and geophysical surveys, the first archaeological excavations ever carried out on the site, the inventory of architectural elements and the gathering of material. Several discoveries allow us to account for the importance acquired by the city, both in the most ancient times and in the Greek, Roman and Islamic periods. For the first time, a scenario of the morphological evolution of the city and its transformations is proposed. This second volume in the series devoted to Qinnasrin provides an original portrait of an outstanding and largely unknown site.